Tenofovir Disoproxil Fumarate Is Superior to Entecavir in Reducing Hepatitis B Surface Antigen for Chronic Hepatitis B in China: 2-Year Comprehensive Comparative Result of a Matched Comparative Study - Yang, Sisi; Ma, Xueqing; Cai, Chengwei; Wang, Huanqiu; Xiao, Fenqiang; Yu, Chengbo (Frontiers in Medicine, 2021)
Aim: Tenofovir disoproxil fumarate (TDF) and entecavir (ETV) are equally recommended as the first-line antiviral treatments for chronic hepatitis B (CHB) at present. We aimed to compare the long-term efficacy and safety between ETV and TDF therapy in CHB patients who had not received nucleoside analog treatment. Method: In this single-center retrospective study, 414 patients who received ETV (290 patients) or TDF (124 patients) therapy at our center from January 2017 to May 2019 were included. To reduce the imbalance of baseline variables, propensity score matching (PSM) was employed to yield 124 pairs of patients at a ratio of 1:1 based on the treatment regimen. Result: After PSM, the cumulative rate of patients who achieved complete virological response (CVR) was not different by drug therapy at each inspection time (1, 3, 6, 12, 18, and 24 months). Subgroup analysis on HBeAg status and level of HBV DNA demonstrated that evolution of proportion of achieving CVR was not significantly different between groups. Despite the insignificant incidence of HBsAg seroclearance in either group, patients in TDF group achieved higher on-treatment HBsAg decline at each inspection time (1, 3, 6, 9, 12, 18, and 24 months), 0.39, 0.51, 0.61, 0.64, 0.68, 0.76, and 0.91 log IU/mL, respectively; while the corresponding reduction were 0.27, 0.37, 0.40, 0.45, 0.48, 0.55, and 0.66 log IU/mL in ETV group (p < 0.05). In subgroup analysis, we found that the significant difference still existed in patients with high baseline HBsAg level (>3 log IU/mL). Additionally, the proportion of patients who achieved on-treatment HBsAg decline >1 log IU/mL in TDF and ETV group was 33.3 and 17.1% (p < 0.01) at the 12th month, 44.4 and 29.5% (p = 0.03) at the 24th month, respectively. Mean increase in serum creatinine from baseline was 0.10 and 0.08 mg/dL in TDF and ETV group (p = 0.11), with no patient experienced acute kidney injury. Conclusions: TDF has higher potency in reducing HBsAg than ETV in this study. Considering the effect still existed in patients with high HBsAg level (>3 log IU/mL), TDF might be a superior therapeutic regimen combining with its relatively safety.